2019
DOI: 10.1021/acs.iecr.9b00158
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Mesoporous Hierarchical Co-Doped ZnO for Highly Sensitive Ethanol Detection

Abstract: The development of highly sensitive gas-sensing materials for the detection of volatile organic compounds at low temperature is vital for gas sensors. Herein, novel mesoporous hierarchical Co-doped ZnO was successfully constructed by calcining layered zinc hydroxide precursors prepared through a facile hydrothermal route. The hierarchical architectures of the precursors were preserved after their conversion to mesoporous Co-doped ZnO through calcination, and the obtained mesoporous hierarchical Co-doped ZnO wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…The transition metal ions doped into the lattice of ZnO by physical or chemical methods [19d,40a,b] . Transition metals exhibit distinct properties compared to other elements due to their unfilled valence orbitals [41] .…”
Section: Metal Element Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition metal ions doped into the lattice of ZnO by physical or chemical methods [19d,40a,b] . Transition metals exhibit distinct properties compared to other elements due to their unfilled valence orbitals [41] .…”
Section: Metal Element Dopingmentioning
confidence: 99%
“…Transition metal doped ZnO can effectively regulate the electronic structure of the material, leading to adjustable the electronic transport efficiency [19a,43a,44a,b] . Mo et al [40a] . reported that the Co doped ZnO is assembled by the thin nanosheets composed of nanoparticles, which exihibits large specific surface area and mesoporous structure.…”
Section: Metal Element Dopingmentioning
confidence: 99%
“…Nanomaterials with porosity plays a vital role in the sensing studies of volatile alcoholic compounds. Porous structures of Ag-functionalized ZnO, Al-doped ZnO, Au loaded WO 3 , 3D-ordered In-doped ZnO, Si@ZnO NPs, Ag loaded graphitic C 3 N 4 , hierarchical mixed Pd/SnO 2 , SnO 2 fibers, hierarchical branched TiO 2 -SnO 2 , and hierarchical Co-doped ZnO were reported for their alcohol sensing utilities [ 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 ]. These porous nanostructures were synthesized by combustion method, nanocasting method, template mediated synthesis, microemulsion method, microdispensing method, solvothermal method, and calcination tactics.…”
Section: Alcoholic Vapor Detection By Miscellaneous Nanostructuresmentioning
confidence: 99%
“…As noted in Table 2 , these meso-/macro-porous nanostructures displays their good responses to alcoholic vapors at different working temperatures (lie between 150 and 350 °C). For example, hierarchical Co-doped ZnO mesoporous structure [ 221 ] revealed its exceptional sensitivity to ethanol (R a /R g = 54 for 50 ppm at 180 °C; response/recovery time = 22 s/53 s) with a LOD of 0.0454 ppm, thereby can be attested as a good candidate for ethanol sensing studies.…”
Section: Alcoholic Vapor Detection By Miscellaneous Nanostructuresmentioning
confidence: 99%
“…The O 1s XPS spectra of Co 3 O 4 samples can be deconvoluted into three peaks, which are assigned to surface lattice oxygen (530.0-530.1 eV), oxygen vacancies (531.1-531.3 eV), and chemisorbed oxygen species (532.3-532.5 eV). 18,29 Table S1 † is the amount of oxygen with different O species of the Co 3 O 4. Generally, the response of the sensing material is signicantly related to the oxygen vacancies.…”
Section: Rsc Advances Papermentioning
confidence: 99%